Funding access and innovation in small businesses - Ronen Harel; Dafna Schwartz; Dan Kaufman (Journal of Risk and Financial Management, 2020)
The study examined the extent to which lack of access to external funding constitutes a barrier to innovation for small businesses operating in traditional industries. The findings indicate that, these businesses do not view lack of access to funding as a barrier to innovation for any of the four types of innovation: product, process, marketing, or organizational. However, for most of the innovations they promoted, the levels of innovation were relatively low, and which naturally entails relatively low risk to businesses. The findings also indicate that, there is a relationship between product and marketing levels of innovation and lack of access to external funding. The study's contribution lies in its focus on small businesses operating in traditional industries—businesses which though, essential to economic growth, have garnered less separate attention in the innovation sphere. The study points to a vicious circle in which these businesses do not promote innovation at high levels that would advance their own competitive advantage and require external funding. Because this funding is not within their reach, they continue promoting low-level innovation, and so on and so forth. The study may practically contribute by assisting policymakers as they draw plans dedicated to supporting innovation in small businesses.
Keywords: 330; access to funding; innovation; small businesses; traditional industry